Analgesic activity of the fractions of the aqueous extract of Ximenia Americana (Linné) (Olacaceae) - tianga yaya, Soro; Ouga Stanislas, Zahoui; Anthelme Semi, Nene-bi (International Journal of Pharmacology and Toxicology, 2016)
This work is the continuation of previous work, during which we investigated the analgesic effects of aqueous extract of Ximenia americana in rats and mice. This work has shown the analgesic action of the aqueous extract of Ximenia americana, effect which seems be due to flavonoids and saponins contained in this total extract. We undertook the fractionation of the crude extract of Ximenia americana, to verify the assumption that the analgesic effect of the aqueous extract from Ximenia americana is due to flavonoids and saponins. To do this we used the fractionation method developed by wagner. This method gave us 6 fractions; we tested on rats and mice. The use of reference molecules such as morphine and phenylbutazone showed the analgesic properties of fractions F2, F4, F6 of the aqueous extract of Ximenia americana.Analgesic activity of the fractions of the aqueous extract ofÂ Ximenia Americana (Linné) (Olacaceae)